Italy and the First Age of Globalization, 1861-1940. - James, H; O'Rourke, K (Nuffield College (University of Oxford), 2012)
The paper presents trade policy as in line with that of other continental European powers, with a move to moderate levels of tariff protection for politically sensitive sectors such as steel and textiles and clothing, but also in agriculture, with levels of protection falling slightly before the First World War. Monetary policy was similarly driven by the constraints of capital scarcity, and by the political priority attached to reducing the cost of funding government debt. The most innovative area was probably in industrial policy, where after the 1880s and again in the 1930s in response to severe shocks, quite creative institutional policies were adopted. In particular financial restructuring was used as an opportunity to reshape the structure of industry.